Influence of Running Dictation on Cooperation and English Storytelling Skills - Siti Ramlah; Victor Maruli Tua L. Tobing; Hetty Purnamasari (Indonesian Journal of Educational Science (IJES), 2026)
At SMAS Miftahul Ulum Al-Baidowi, the approach to English learning largely relies on teacher-led techniques, which leads to inadequate development of students' speaking abilities and teamwork skills. This research focused on analyzing how the Running Dictation teaching method influences the collaborative skills and storytelling abilities in English of tenth-grade learners. A quasi-experimental design was utilized, specifically a Nonequivalent Control Group Design, with a sample of 54 students. Information was gathered via surveys and storytelling assessments, then processed through independent sample t-tests and MANOVA. The results showed a notable effect of the Running Dictation teaching method, presenting a significance value of 0.000 (less than 0.05). The experimental group recorded a greater average in collaborative skills (17.62) and English storytelling (21.11) when compared to the control group, which had average scores of 12.66 and 15.14, respectively. These findings suggest that the Running Dictation teaching method successfully enhances both the social and academic skills of students. Consequently, it is recommended that educators use this method as an alternative approach to foster engaged, communicative, and cooperative learning.